2021
DOI: 10.3390/cells10071762
|View full text |Cite
|
Sign up to set email alerts
|

Viral MicroRNAs Encoded by Nucleocapsid Gene of SARS-CoV-2 Are Detected during Infection, and Targeting Metabolic Pathways in Host Cells

Abstract: MicroRNAs (miRNAs) are critical regulators of gene expression that may be used to identify the pathological pathways influenced by disease and cellular interactions. Viral miRNAs (v-miRNAs) encoded by both DNA and RNA viruses induce immune dysregulation, virus production, and disease pathogenesis. Given the absence of effective treatment and the prevalence of highly infective SARS-CoV-2 strains, improved understanding of viral-associated miRNAs could provide novel mechanistic insights into the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 62 publications
4
41
2
Order By: Relevance
“…As compared to other studies of SARS-CoV-2, we did not detect svRNAs derived from the N gene (10, 12), which suggests that the functions of those is not related to RNAi pathway. Interestingly, vmiR-5p was also detected by Meng and colleagues, but was not selected for further validation (12).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…As compared to other studies of SARS-CoV-2, we did not detect svRNAs derived from the N gene (10, 12), which suggests that the functions of those is not related to RNAi pathway. Interestingly, vmiR-5p was also detected by Meng and colleagues, but was not selected for further validation (12).…”
Section: Discussioncontrasting
confidence: 82%
“…There are multiple examples of svRNAs expressed by RNA viruses, such as influenza (42), enterovirus 71 (43), Hepatitis C (44), hepatitis A (45), Polio (44), Dengue (44, 46), Vesicular Stomatitis (44), West Nile (44, 47), coronaviruses (10-12) and retroviruses (48, 49). It has been suggested that some svRNAs function through the host-cell RNAi pathway (12, 44, 45), but most proposed roles are independent of this machinery (10, 11, 42, 43, 50). As compared to other studies of SARS-CoV-2, we did not detect svRNAs derived from the N gene (10, 12), which suggests that the functions of those is not related to RNAi pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These concepts were explored in a study in which the authors started by infecting cultured cell lines with SARS-CoV-2 [ 99 ]. RNA sequencing was then used to identify a swathe of virus-derived small RNAs.…”
Section: Interactions Between Host and Sars-cov-2-derived Ncrnasmentioning
confidence: 99%